2023
DOI: 10.3389/fpls.2023.1140596
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of CmWRKY15-1 to chrysanthemum white rust based on TRV-VIGS

Abstract: Chrysanthemum White Rust (CWR) caused by Puccinia horiana Henn. is a major disease in the production process of chrysanthemum, which is widely spread all over the world and can be called “cancer” of chrysanthemum. To clarify the disease resistance function of disease resistance genes can provide a theoretical basis for the utilization and genetic improvement of chrysanthemum resistant varieties. In this study, the resistant cultivar ‘China Red’ was used as the experimental material. We constructed the silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Many studies have been published about the fungal diseases as epidemic diseases caused by rust and Verticillium spp. on chrysanthemum such as Sumitomo et al [ 16 ], Bi et al [ 17 ], Gao et al [ 18 ], Munilakshmi et al [ 19 ], and Chen et al [ 20 ]. It is reported that V. dahliae can colonize the vascular tissues of infected plants which may persist in the soil for up to more than 10 years, even in the absence of a host [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published about the fungal diseases as epidemic diseases caused by rust and Verticillium spp. on chrysanthemum such as Sumitomo et al [ 16 ], Bi et al [ 17 ], Gao et al [ 18 ], Munilakshmi et al [ 19 ], and Chen et al [ 20 ]. It is reported that V. dahliae can colonize the vascular tissues of infected plants which may persist in the soil for up to more than 10 years, even in the absence of a host [ 15 ].…”
Section: Introductionmentioning
confidence: 99%